PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL DAN ASIMETRI INFORMASI UNTUK MENGATASI KECURANGAN AKUNTANSI (STUDI PADA SKPD KOTA MOJOKERTO) - OCTAKISTI, RENATA (Jurnal Akuntansi AKUNESA, 2016)
Abstract Weak internal control and information asymmetry may be an opportunity for individuals or groups to commit accounting fraud. Fraud can be reduced and even prevented by creating a work atmosphere of mutual help to each other, openness, and their culture to be honest. The purpose of this study was to determine whether the internal control and the information asymmetry effect on accounting fraud. The approach adopted is a quantitative research using primary data sources in the form of questionnaires distributed in 21 SKPD Mojokerto. These results indicate that the effect on the internal control of the accounting fraud and the information asymmetry does not affect the accounting fraud.   Keywords: internal control, information asymmetry, accounting fraud.